A preliminary study on correlation between stress and Satva sara among students of ayurveda college - Resmy A Raj; M Abhilash; Chitra M Gawande; Jeevan Jagadeesh Kulkarni (Wolters Kluwer Medknow Publications, 2021)
Introduction: Stress is a physical, mental, or emotional factor that causes physical or psychological tension. Various researches conducted in the field of stress revealed that stress is the common inhibitor on academic performances and students in professional colleges exposes to higher levels of stressors than their peers. In addition to stressors of everyday life, the medical students must deal with stressors such as examinations, chances of failure, lack of leisure time, workload, relationships with peers, etc. Therefore, early detection and estimation of stress and its intervention is very much essential to prevent or minimize the effects of distress on the students in future. Methods: 200 students of 1st and 2nd year BAMS were selected for the study. Their stress as evaluated with perceived stress scale-10. Satva sara was evaluated with a validated Satvasara assessment tool. Statistical tests were employed to find out the prevalence of stress and correlational studies were conducted to find out the relationship between stress and Satvasarata. Results and Conclusion: About 80% of Ayurveda College students were recorded as having moderate stress, 6% has mild and remaining 14% suffer from high perceived stress. A significant negative correlation is found in between stress and Satvasara with a spearman's correlation coefficient of - 0.332 and P < 0.001. Implementing methods to enhance the Satvasara of subjects with behavioral therapies like chanting mantra, yoga, meditation, pranayama could be more useful and effective in controlling stress among medical students.